Privacy Preservation Techniques in V2X Ecosystems: Safeguarding Individual Privacy in Connected Vehicle Environments (Journal of Artificial Intelligence Research, 2024)
In recent years, the advancement of connected vehicle technologies has revolutionized transportation systems worldwide. The seamless exchange of data between vehicles, infrastructure, and other entities has led to significant improvements in transportation efficiency, safety, and convenience. However, alongside these benefits, concerns have emerged regarding the privacy implications of Vehicle-to-Everything (V2X) ecosystems.The proliferation of V2X communication systems raises fundamental questions about the protection of individuals' privacy rights. As vehicles become increasingly interconnected, vast amounts of data are exchanged, including sensitive information about drivers, passengers, and their surroundings. The potential for misuse or unauthorized access to this data has sparked discussions about the need for robust privacy preservation techniques within V2X environments.This article aims to address these concerns by exploring various privacy preservation techniques tailored to V2X ecosystems. Specifically, the article examines methods for anonymizing data, minimizing personal data collection, and ensuring the implementation of robust and transparent user consent mechanisms.Anonymization techniques play a crucial role in protecting individual privacy within V2X ecosystems. By dissociating personal identifiers from the transmitted data, anonymization methods such as pseudonymization, encryption, and data aggregation aim to prevent the identification of individuals while still allowing for the exchange of valuable information.Furthermore, minimizing personal data collection is essential for reducing privacy risks in V2X environments. By implementing selective data collection mechanisms and adhering to data minimization principles, stakeholders can limit the collection of unnecessary information and mitigate the potential for privacy breaches.Ensuring robust and transparent user consent mechanisms is another key aspect of privacy preservation in V2X ecosystems. Empowering users to make informed decisions about the sharing and utilization of their personal data fosters trust and accountability within the system. By incorporating privacy-by-design principles into V2X systems, developers can prioritize privacy considerations from the outset, thereby enhancing user confidence in the protection of their privacy rights.In conclusion, as connected vehicle technologies continue to evolve, it is imperative to prioritize the preservation of individual privacy within V2X ecosystems. By implementing a combination of anonymization techniques, data minimization strategies, and robust user consent mechanisms, stakeholders can mitigate privacy risks and uphold privacy standards in the increasingly interconnected world of transportation.
Keywords: V2X ecosystems; privacy preservation; anonymization techniques; data minimization; user consent mechanisms; connected vehicles; privacy-by-design